On testing conditional moment restrictions: The canonical case - Gautam Tripathi; Yuichi Kitamura (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
Let (x, z) be a pair of random vectors. We construct a new smoothed empirical likelihood based test for the hypothesis that E(z|x) a.s. = 0, and show that the test statistic is asymptotically normal under the null. An expression for the asymptotic power of this test under a sequence of local alternatives is also obtained. The test is shown to possess an optimality property in large samples. Simulation evidence suggests that it also behaves well in small samples.
urn:nbn:de:kobv:11-10048146
Keywords: 330